Association of urinary ketamine and APOA1 levels with bladder dysfunction in ketamine abusers revealed via proteomics and targeted metabolite analyses - Liu, Jo-Chuan; Chen, Yi-Ting; Hsieh, Ya-Ju; Wu, Chia-Chun; Huang, Ming-Chyi; Hsu, Yu-Chao; Wu, Chun-Te; Chen, Chih-Ken; Dash, Srinivas; Yu, Jau-Song (Scientific reports, 2021)
Chronic ketamine abuse is associated with bladder dysfunction and cystitis. However, the effects of ketamine abuse on the urinary proteome profile and the correlations among urinary proteins, urinary ketamine (and metabolites) and clinicopathological features of ketamine-induced bladder dysfunction remain to be established. Here, we recruited 56 ketamine abusers (KA) and 40 age-matched healthy controls (HC) and applied the iTRAQ-based proteomics approach to unravel quantitative changes in the urine proteome profile between the two groups. Many of the differentially regulated proteins are involved in the complement and coagulation cascades and/or fibrotic disease. Among them, a significant increase in APOA1 levels in KA relative to control samples (392.1 ± 59.9 ng/ml vs. 13.7 ± 32.6 ng/ml, p < 0.0001) was detected via ELISA. Moreover, urinary ketamine, norketamine and dehydronorketamine contents (measured via LC-SRM-MS) were found to be positively correlated with overactive bladder syndrome score (OABSS) and APOA1 levels with urinary RBC, WBC, OABSS and numeric pain rating scale in KA. Collectively, our results may aid in developing new molecular tool(s) for management of ketamine-induced bladder dysfunction. Moreover, information regarding the differentially regulated proteins in urine of KA provides valuable clues to establish the molecular mechanisms underlying ketamine-induced cystitis.